An Optimized Design of Single-Channel Beta-Gamma Coincidence Phoswich Detector by Geant4 Monte Carlo Simulations. (14th May 2011) - Zhang, Weihua; Mekarski, Pawel; Bean, Marc; Yi, Jing; Ungar, Kurt
Abstract : An optimized single-channel phoswich well detector design has been proposed and assessed in order to improve beta-gamma coincidence measurement sensitivity of xenon radioisotopes. This newly designed phoswich well detector consists of a plastic beta counting cell (BC404) embedded in a CsI(Tl) crystal coupled to a photomultiplier tube. The BC404 is configured in a cylindrical pipe shape to minimise light collection deterioration. The CsI(Tl) crystal consists of a rectangular part and a semicylindrical scintillation part as a light reflector to increase light gathering. Compared with a PhosWatch detector, the final optimized detector geometry showed 15% improvement in the energy resolution of a 131m Xe 129.4 keV conversion electron peak. The predicted beta-gamma coincidence efficiencies of xenon radioisotopes have also been improved accordingly.